Teaching of Primary School Social Studies in Greece: An Analysis of Curriculum Implementation - Ivrinteli, Maria (Advances in Social Sciences Research Journal, 2023)
This study investigates how teachers and students assess curriculum implementation in social studies courses at primary school in Greece. Through a survey questionnaire teachers were asked to express their perceptions of the curriculum guidelines, materials and instructional and evaluation procedures. The results indicated that teachers find little help in curriculum guidelines in terms of determining instructional methods, materials and evaluation strategies they use in their class. The most common approach to classroom instruction in social studies is lecturing and discussion followed by recitation. The use of materials other than the course textbook is very limited, and textbook-related activities are the most common mode of homework assignment given to the students. Oral exams and short-answer tests are the most common mode of student evaluation in social studies classes.